ANALISIS BEBAN KERJA TERHADAP KINERJA TENAGA KERJA REKAM MEDIS DI RSUD PETALA BUMI - Widya Azzari (LPPM Universitas Awal Bros, 2021)
Workload is the effort that must be expended by someone to fulfill the “demand” of the job. The capacity is the ability or human capacity that can be measured from a person’s physical and mental condition. The workload in question is a measure (portion) of the limited operator capacity required to perform a particular job. If the workload is excessive, it will reduce the quality of life (fatigue) and the quality of work of the person and can also affect occupational safety and health. Method : what is done is observation and documentation . Results: the results obtained based on the journals discussed are that there are better results in improving employee performance Keyword : Workload, Medical records, Performance